First insights into the transfer of marketing know-how from Western firms to enterprises in Central and Eastern Europe: A qualitative study - Roger Bennett (Journal for East European Management Studies, 1998)
This paper reports the results of case study research into the methods employed by 12 large UK-based companies when transferring marketing know-how to Central and East European (CEE) joint venture partner firms. Propositions derived from transactions cost analysis and theories concerning the optimal means for transmitting technical information between organisations are applied to the data, and the usefulness of a number of collateral hypotheses are assessed. It is concluded that certain elements of transactions cost theory stand up well in the CEE business context, but that the practical devices adopted by Western enterprises when transferring marketing know-how to foreign CEE partners need to be improved. – – Dieser Artikel faßt die Ergebnisse von Fallstudienuntersuchungen bezüglich der Methodik des Marketing-know-how-Transfers nach Mittel- und Osteuropa zusammen. Dazu wurden 12 große britische Unternehmungen und deren Joint- Venture-Partner in Mittel- und Osteuropa untersucht. Es wurden Ansätze auf der Basis der Transaktionskostenanalyse und Theorien zur optimalen Übertragung technischer Informationen auf die Daten angewandt und eine Reihe weiterer Hypothesen geprüft. Einige Elemente der Transaktionskostenanalyse erwiesen sich im gegebenen Kontext als sehr geeignet. Die praktische Umsetzung des Know-how-Transfers bedarf aber noch erheblicher Verbesserungen.
Keywords: 650